Borrowing by developing countries on the Euro-currency market - Wellons, Philip A. (Paris : Development Centre of the Organisation for Economic Co-operation and Development ; [Washington, D.C. : sales agent, OECD Publications Center], 1977)
This book examine the experience of the borrowers countries despite the flow of Eurocurrency loans to borrowers in Africa, Asia, and Latin America, little is known about how and why the funds were raised. It highlights the challenges inherent in this issues and proffered possible solution with supportive data.
Includes bibliographical references.
usc 15/08/18
Loans
Keywords: Euro-dollar market